2019
DOI: 10.3233/rnn-190948
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive current stimulation in vision recovery: a review of the literature

Abstract: Background: Around 253 million people worldwide suffer from irreversible visual damage. Numerous studies have been carried out in order to unveil the effects of electrical stimulation (ES) as a useful tool for rehabilitation for different visual conditions and pathologies. Objective: This systematic review aimed to 1) examine the current evidence of ES efficacy for the treatment of visual pathologies and 2) define the corresponding degree of the recommendation of different ES techniques. Methods: A systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 56 publications
0
18
2
6
Order By: Relevance
“…Non-invasive visual cortex stimulation studies have reported varying fellow eye effects. Studies using inhibitory stimulation protocols (1 Hz rTMS and continuous theta burst stimulation; cTBS) have reported reduced fellow eye contrast sensitivity 35 , 36 whereas those using excitatory protocols (anodal tDCS and tRNS) 24 , 42 , including the present study, observed improvements. This pattern of results is consistent with the homeostasis hypothesis which predicts relatively impaired fellow eye function following inhibitory stimulation and does not rule out improved fellow eye function following excitatory stimulation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Non-invasive visual cortex stimulation studies have reported varying fellow eye effects. Studies using inhibitory stimulation protocols (1 Hz rTMS and continuous theta burst stimulation; cTBS) have reported reduced fellow eye contrast sensitivity 35 , 36 whereas those using excitatory protocols (anodal tDCS and tRNS) 24 , 42 , including the present study, observed improvements. This pattern of results is consistent with the homeostasis hypothesis which predicts relatively impaired fellow eye function following inhibitory stimulation and does not rule out improved fellow eye function following excitatory stimulation.…”
Section: Discussioncontrasting
confidence: 56%
“…Transcranial electrical stimulation (tES) refers to a suite of non-invasive neuro-modulation techniques including transcranial direct current stimulation (tDCS), transcranial alternating current stimulation (tACS) and transcranial random noise stimulation (tRNS) that may enhance plasticity in targeted regions of the human brain 21 23 , including the visual cortex 24 26 . Currently, tES methods are being investigated as a potential neurorehabilitation tool for disorders including stroke 27 30 , chronic pain 31 , 32 and tinnitus 33 , 34 and there is growing interest in the use of tES and transorbital stimulation to treat disorders of vision (see 35 38 for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive visual cortex stimulation studies have reported varying fellow eye effects. Studies using inhibitory stimulation protocols (1 Hz rTMS and continuous theta burst stimulation; cTBS) have reported reduced fellow eye contrast sensitivity [35,36] whereas those using excitatory protocols (anodal tDCS and tRNS) [24,40], including the present study, observed improvements. This pattern of results is consistent with the homeostasis hypothesis which predicts relatively impaired fellow eye function following inhibitory stimulation and does not rule out improved fellow eye function following excitatory stimulation.…”
Section: Trns-induced Improvements In Contrast Sensitivitycontrasting
confidence: 53%
“…Currently, tES methods are being investigated as a potential neurorehabilitation tool for disorders including stroke [27][28][29][30], chronic pain [31,32] and tinnitus [33,34] and there is growing interest in the use of tES to treat disorders of vision (see [35,36] for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effects of each tDCS method, it is suggested that bihemispheric tDCS has a more significant effect on chronic stroke [ 6 8 ]. Moreover, the positive effect of each tDCS approach on stroke motor recovery has been elucidated by previous studies [ 9 13 ]. Notably, recent systematic reviews reported the improvement of upper limb (UL) sensorimotor functions and improvement of activities of daily living following tDCS in post-stroke individuals [ 8 10 , 14 ].…”
Section: Introductionmentioning
confidence: 94%